The impact of intergenerational programs on social capital in Japan: a randomized population-based cross-sectional study - Murayama, Yoh (BMC Public Health, 2019)
BACKGROUND: Over the last several decades, social isolation and loneliness among older adults have posed an increasingly urgent challenge due to the rapidly aging population in Japan. To remedy the situation, many communities have introduced intergenerational programs. However, few studies have investigated the benefits of social capital across generations as a result of intergenerational interaction between children and older generations. Therefore, we aim to ascertain the degree to which intergenerational programs that take root in a community will affect the social capital of all generations in the community. METHODS: We focus our research on one specific program, REPRINTS, an intergenerational health promotion program for older adults that has been active for over 10 years in Tama Ward, Kawasaki City, Kanagawa Prefecture. We conducted a population-based cross-sectional study of residents between the ages of 20 and 84 years who were randomly selected from the basic resident register. Approximately 2500 residents were selected, of which 978 responded; data from 891 respondents were analyzed. RESULTS: Hierarchical linear modeling suggests that the duration of programs was a significant community-level indicator of neighborhood trust. At the individual level, people between 30 and 59 years of age and people over 60 years of age have more positive effects on neighborhood trust than do people between 20 and 39 years of age. CONCLUSIONS: The ongoing intergenerational programs between older citizens and children can enforce neighborhood trust, thus strengthening a community’s intergenerational ties. The REPRINTS program has been developed through cooperation with local citizens, senior volunteers, and teachers from the community. Its collaborative nature ensures longevity and continuous growth in a community. It is challenging to create long-term intergenerational programs that take root in communities, making persistence and collaboration a crucial factor in fruitful intergenerational relationships. Overall, ongoing intergenerational program implementation associates with building social capital, thereby strengthening potential intergenerational ties and promote mutual support among local residents which will reduce or prevent social isolation among older.